2002
DOI: 10.1055/s-2002-32665
|View full text |Cite
|
Sign up to set email alerts
|

New Characteristics of Anti-Factor VIII Inhibitor Antibody Epitopes and Unusual Immune Responses to Factor VIII

Abstract: Treatment of individuals with severe hemophilia A by plasma-derived or recombinant factor VIII leads to the production of anti-factor VIII antibodies in approximately 30% of such patients. Because some of these antibodies inactivate factor VIII, they are considered a major factor in preventing optimal therapeutic treatment. Factor VIII is a cofactor that must bind to factors IX and X and phospholipids in order for normal blood coagulation to occur. The inhibition of factor VIII activity is due to binding by an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 30 publications
0
9
0
1
Order By: Relevance
“…The A2, A3, C1 and especially the C2 domain are reported to comprise immunogenic epitopes [20][21][22][23][24]. These epitopes contain peptide sequences important for FIX binding (A2 and A3 domain) as well as phospholipid and VWF attachment (C1 and C2 domain) [26]. These epitopes contain peptide sequences important for FIX binding (A2 and A3 domain) as well as phospholipid and VWF attachment (C1 and C2 domain) [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The A2, A3, C1 and especially the C2 domain are reported to comprise immunogenic epitopes [20][21][22][23][24]. These epitopes contain peptide sequences important for FIX binding (A2 and A3 domain) as well as phospholipid and VWF attachment (C1 and C2 domain) [26]. These epitopes contain peptide sequences important for FIX binding (A2 and A3 domain) as well as phospholipid and VWF attachment (C1 and C2 domain) [26].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Hay et al found significant immunogenicity of the C1/C2 junction in patients with non-severe HA due to missense mutations in this part of FVIII [25]. These epitopes contain peptide sequences important for FIX binding (A2 and A3 domain) as well as phospholipid and VWF attachment (C1 and C2 domain) [26]. Thus, the LC may be of overall greater immunogenicity than the HC, especially the C1/C2 domain that is involved in binding to VWF and phospholipids.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of inhibitors in the haemophilia population is between 5% and 7%, with the highest incidence, approximately 30%, observed among severe haemophiliacs [3–5]. It has been reported that VWF‐containing concentrates elicit a lower frequency of inhibitors, are less inhibited by inhibitors directed against the C2 region, which also binds the VWF, and appear to be more effective when used to induce immune tolerance [6–11]. It has been observed that most inhibitors display a wide range of immunoreactivity when tested against a panel of commercial FVIII concentrates, and the measured inhibitor titres vary widely depending on the concentrates tested [12–14].…”
Section: Introductionmentioning
confidence: 99%
“…Although IgG4 is frequently the major component of anti‐FVIII antibodies, all IgG subclasses have been found [3,4]. While the antibodies against FVIII are well characterized [5–8], limited information is available on the regulation of the antibody response. In particular, the reason why some patients develop antibodies while others do not is far from clear.…”
Section: Transgenic Mouse Models For Deciphering Inhibitor Mechanismsmentioning
confidence: 99%